Creating Safe Schools: The Importance of Peers in Bully Prevention Programs - Smolleck, Lori Ann (Advances in Social Sciences Research Journal, 2018)
The purpose of this study was to review the existing literature on bullying and investigate prevention programs currently in existence. Furthermore, this research examined the Creating a Safe School (CASS) program used within a middle school in Central Pennsylvania. Because CASS utilizes peer mentors and educators, this study also examined the importance of peers in adolescent’s lives and the importance of using peers as a way to create safe schools. Methods for constructing effective and efficient bullying prevention programs are discussed using the data analysis, as well as current research in the field. The overall aim of this research study is to lead educators, administrators, parents, and other individuals working with children and adolescents toward a better understanding of the various types of bullying, how and why bullying occurs, as well as how bullying can be addressed and prevented.